Model Pendidikan Islam Masa Klasik - Khair, Ummul; Asha, Lukman (Akademika : Jurnal Keagamaan dan Pendidikan, 2023)
The world of education has actually been around since humans existed, and continues to develop in accordance with social and cultural developments in humans themselves. Likewise with the history of Islamic education, which in essence cannot be separated from Islam and its people. In the long course of history, Islamic education has gone through various eras and various regions, meaning that Islamic education has continued to experience changes and developments since the early days of Islam being developed by the Prophet, up to the modern era like today. In a period of development that has gone through several periods, Islamic education has given birth to various ideas from Islamic education figures that emerged from Muslim figures and people, from time to time changing and developing, but in general the thoughts are related to matters that talk about principles. and the goals of educators, students, material media (curriculum), methods, models, Islamic education institutions and socio-economic background, political and physical environment that influence the Islamic education process.